Analisis Strategi Promosi Pembiayaan Murabahah dalam Meningkatkan Jumlah Anggota di BMT Al-Iqtishady Kota Mataram: Studi Kasus di BMT Al-Iqtishady Kota Mataram - Nunung Harianti; Muslihun; Pongky Arie Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
BMT Al-Iqtishady Mataram City is a sharia-based financial institution. This company operating in the service sector uses 2 promotional media, namely online media and offline media. The online media used by BMT is websites, Instagram and Facebook. Meanwhile, for offline media, BMT uses brochures. This research is qualitative research that is descriptive qualitative in nature, trying to describe the research results obtained in the field. The types of data used in this research are primary and secondary data with the data sources used consisting of; General Manager, Customer Service (CS), Funding, PPOB Unit Manager, and Finance with data collection techniques used by researchers in the form of Non-Participant Observation, Structured Interviews, and Documentation. The data obtained is then processed in the form of words which are then expressed in the form of a description or narrative. The results of this research are financing promotion strategies, especially murabahah, BMT Al-Iqtishady does not carry out specific promotions per product. However, BMT carries out overall promotions where the main aim is to increase the number of members. Because, joining the community as members is one of the requirements that must be met if financing is to be carried out.